Accounting for Waqf: A Survey on Scopus-based Literatures - Uula, Mimma Maripatul; Kassim, Siti Fatimah Mohd (Accounting and Sustainability, 2023)
This study aims to see the development of research on the topic of "Waqf Accounting" and research plans that can be done based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Waqf Accounting" which comes from the Scopus database with a total of 40 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Waqf Accounting" research development in the world. The results of the study found that in bibliometric author mapping the author who published the most research with the theme "Waqf Accounting" was Gürsoy Ç. Furthermore, based on bibliometric keyword mapping, there are 4 clusters that can be a research path with topics related to Management of Waqf Assets and Waqf Accounting, Waqf Accounting Awareness, Business Impact and Waqf Accounting, and Challenges in Waqf Accounting Reporting. Furthermore, the most used words are waqf institution, accountability, Islamic accounting, waqf accounting, reporting, and technology.